Method for regenerating lithium iron phosphate positive electrode material from waste battery black powder
Through one-step hydrothermal method and carbonization roasting process, the recycling process of waste lithium iron phosphate batteries is simplified, and the efficient utilization of lithium, iron and phosphorus resources is achieved, the problem of low utilization rate of iron phosphate resources is solved, and the battery performance and resource recycling efficiency is improved. .
Patent Information
- Application Number
- CN202411193648.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-01-10
AI Technical Summary
In the recycling of waste lithium iron phosphate batteries, the utilization rate of iron phosphate resources is relatively low, the process flow is complex and the cost is high, resulting in resource waste and environmental pollution problems.
The modified lithium iron phosphate positive electrode material is prepared by one-step hydrothermal method and carbonized baking. Through leaching, impurity removal and hydrothermal synthesis processes, the process flow is simplified to achieve the synchronous and efficient utilization of lithium, iron and phosphorus resources.
It reduces process costs and time, improves resource utilization efficiency, improves the electrochemical performance and cycle life of regenerated lithium iron phosphate materials, and solves the problems of resource waste and environmental pollution.
Smart Images

Figure CN119284854A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling waste lithium-ion batteries, and in particular to a method for regenerating lithium iron phosphate positive electrode materials from black powder of waste lithium iron phosphate batteries. Background Art
[0002] With the widespread application of lithium iron phosphate batteries in mobile communications, portable electronic devices and electric vehicles, their usage has increased dramatically, and the problem of waste battery disposal has become increasingly prominent. However, the service life of lithium iron phosphate batteries is usually 5 to 8 years. If the battery is not properly disposed of at the end of its service life, it will not only waste resources, but also cause serious pollution to the environment.
[0003] Therefore, recycling lithium iron phosphate batteries is of great significance. First, lithium iron phosphate batteries contain harmful substances. If they are discarded at will or handled improperly, they may cause pollution to the environment. Recycling lithium iron phosphate batteries can reduce the emission of harmful substances and reduce the impact on the environment. Second, lithium iron phosphate batteries also contain valuable elements, such as lithium, iron, phosphorus, etc. By recycling these high-value elements, resources can be reused and dependence on natural resources can be reduced.
[0004] In the research on the recycling of waste lithium iron phosphate batteries, most of the research focuses on improving the recovery rate of lithium, while the utilization rate of ferrophosphorus resources is relatively low. For example, a method for recovering lithium from lithium iron phosphate mentioned in the patent application with application number 202210256273.7 uses heteropoly acid as a medium for electrolytic oxidation and reduction. Although a lithium-rich solution is prepared, the ferrophosphorus enriched on the anode side is not effectively utilized after impurities are removed; a method for recovering regenerated lithium carbonate from lithium iron phosphate waste mentioned in application number 202210528476.7 obtains a lithium-rich solution by leaching and removing impurities with alkaline solution, and the whereabouts of ferrophosphorus resources are not explained too much. Nowadays, the price of lithium carbonate is going down, and ferrophosphorus resources also need to be fully utilized to increase overall profits and reduce the amount of solid waste treatment. The difficulty in utilizing ferrophosphorus resources after lithium extraction in the industry is mainly due to two factors. First, there is no obvious advantage in the quality of ferrophosphorus regenerated iron phosphate, and the product price is low; second, the process flow of ferrophosphorus regenerated iron phosphate is long, impurities are difficult to remove, and the cost of raw materials is high.
[0005] At present, the technology of regenerating lithium iron phosphate positive electrode materials from waste lithium iron phosphate batteries is mainly divided into two methods: physical repair and hydrometallurgy. Although the physical method has a lower process cost, it has high requirements on the quality of raw materials, and the electrochemical performance after repair cannot be fully restored. Although hydrometallurgy has lower requirements on the quality of raw materials and can obtain regenerated lithium iron phosphate that meets commercial standards, the process cost is relatively high. For example, a patent application with application number 202310182897.3 discloses a method for regenerating positive electrode materials of waste lithium iron phosphate batteries. This method combines physical repair and hydrometallurgy. The process is cumbersome and the recovery rate of the final product is low. Therefore, it is urgent to develop a production process for regenerated lithium iron phosphate positive electrode materials with simple process and high efficiency. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a simple and efficient method for regenerating lithium iron phosphate positive electrode materials from waste lithium iron phosphate battery black powder. The present invention prepares modified lithium iron phosphate positive electrode materials through a one-step hydrothermal method and carbonization roasting, shortens the process flow, and realizes the simultaneous and efficient utilization of lithium, iron and phosphorus resources.
[0007] The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder comprises the following steps: S1, leaching: put the waste lithium iron phosphate battery black powder in a beaker, add deionized water for homogenization, add sulfuric acid to adjust the pH value and react, and filter to obtain a leachate rich in lithium, iron, phosphorus and impurity elements; S2, impurity removal: according to the impurity copper content in the leachate obtained in step S1, 1-3 times the molar amount of reduced iron powder is added to remove copper impurities by replacement reaction, the pH value is adjusted to 2-6 with a pH regulator, and according to the impurity aluminum content in the leachate, 1-6 times the molar amount of a complexing agent is added to remove impurities such as aluminum and titanium; S3, synthesis: placing the solution after impurity removal in step S2 in a reactor, adjusting the molar ratio of Li:Fe:P in the solution to 1-3:1:1, adding 0-3 mmol antioxidant and 0-800 mg carbon coating agent, stirring evenly and sealing the solution and placing it in an oven for hydrothermal reaction, and filtering and drying the solution after the reaction is completed and the temperature is naturally lowered to obtain a lithium iron phosphate precursor; S4, carbonization: placing the lithium iron phosphate precursor obtained in step S3 in a crucible, transferring it to a sintering device, heating it to 400-600°C at a rate of 5-10°C / min under the protection of an inert atmosphere, keeping it at that temperature for 1-4 hours, and then naturally cooling it to room temperature to obtain modified lithium iron phosphate.
[0008] Preferably, in step S1, the solid-liquid ratio of waste lithium iron phosphate battery black powder to deionized water is 100-200 g / L.
[0009] Further preferably, in step S1, the solid-liquid ratio of waste lithium iron phosphate battery black powder to deionized water is 160-200 g / L.
[0010] Preferably, in step S1, the homogenization treatment time is 30-45 min.
[0011] Preferably, in step S1, the pH value is adjusted to 1-3 and the reaction time is 1-3 h.
[0012] More preferably, in step S1, the pH value is adjusted to 1-2 and the reaction time is 1-2 h.
[0013] Preferably, in step S2, the molar ratio of the added amount of reduced iron powder to the impurity copper is 1-2.
[0014] Preferably, in step S2, the pH adjuster includes aqueous ammonia, sodium hydroxide or sodium carbonate solution.
[0015] Preferably, in step S2, the complexing agent includes hydrofluoric acid, sodium fluoride or ammonium fluoride.
[0016] Preferably, in step S3, the molar ratio of Li:Fe:P in the adjustment solution is 1-2:1:1.
[0017] Preferably, in step S3, the antioxidant comprises ascorbic acid, sodium ascorbate or isoascorbic acid.
[0018] Preferably, in step S3, the amount of the antioxidant added is 1-2 mmol.
[0019] Preferably, in step S3, the carbon coating agent includes polyvinyl pyrrolidone, dopamine or glucose.
[0020] Preferably, in step S3, the amount of the carbon coating agent added is 100-400 mg.
[0021] Preferably, in step S3, the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 2-6 h.
[0022] More preferably, in step S3, the temperature of the hydrothermal reaction is 160-180° C., and the reaction time is 2-5 h.
[0023] Preferably, in step S4, the inert atmosphere includes nitrogen, argon or a mixture of argon and hydrogen.
[0024] Preferably, in step S4, the heating rate is 5-9°C / min, the insulation temperature is 450-600°C, and the insulation time is 1-3 h.
[0025] The modified lithium iron phosphate is used as a positive electrode material in a lithium ion battery.
[0026] The modified lithium iron phosphate is used as a positive electrode material in a lithium-ion battery, comprising the following assembly steps: mixing the modified lithium iron phosphate with an adhesive and a conductive agent in a mass ratio of 92:4:4, slurrying them evenly in an N-methylpyrrolidone solvent, coating them on an aluminum foil, drying them at 120°C and punching them out, and vacuum drying them at 80°C to use them as a positive working electrode, using a metal lithium sheet as a counter electrode, and using 1.0 M LiPF6 in DEC:DMC:EC (V:V:V=1:1:1) with 1%VC as an electrolyte system to assemble a button cell (half cell).
[0027] Preferably, the adhesive comprises polyvinylidene fluoride (PVDF).
[0028] Preferably, the conductive agent comprises Super P Li, which is a high-purity and structured carbon black powder.
[0029] Compared with the prior art, the present invention has the following technical effects: 1. The method for regenerating lithium iron phosphate positive electrode materials from waste lithium iron phosphate battery black powder provided by the present invention simplifies the process flow, reduces energy consumption and time costs, and improves economic benefits through a one-step hydrothermal method and carbonization roasting. This is not only conducive to promoting the development of the waste battery recycling industry, but also can promote the green transformation and upgrading of the lithium-ion battery industry chain.
[0030] 2. The present invention realizes the simultaneous and efficient utilization of lithium, iron and phosphorus resources. In the traditional recycling process, these elements often need to be extracted and purified separately, and the extraction rate is not high, resulting in waste of resources. The present invention retains these valuable elements to the maximum extent by directly regenerating lithium iron phosphate, thereby improving the comprehensive utilization efficiency of resources.
[0031] 3. The method for regenerating lithium iron phosphate positive electrode materials from waste lithium iron phosphate battery black powder provided by the present invention has good consistency in the liquid phase synthesis process, and the coating agent used has good film-forming properties, which can achieve uniform coating of lithium iron phosphate materials, effectively improve the conductivity of lithium iron phosphate, and avoid corrosion problems caused by direct contact between electrolyte and positive electrode materials. The regenerated lithium iron phosphate, as a positive electrode material for lithium-ion batteries, exhibits excellent electrochemical properties, including higher charge and discharge efficiency and longer cycle life.
[0032] 4. The present invention realizes the effective recovery and reuse of waste lithium iron phosphate batteries, and provides a practical solution to the problem of waste battery disposal. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the process flow of an embodiment of the invention. DETAILED DESCRIPTION
[0034] The following will be combined with specific embodiments to clearly and in detail describe the technical solutions provided by the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, and other embodiments obtained by relevant personnel in the field without making creative improvements and labor premises all belong to the scope of protection of the present invention. The raw materials used in the embodiments can be purchased commercially or prepared by conventional methods.
[0035] The quality of the used lithium iron phosphate battery black powder is shown in Table 1: Table 1. Statistical table of main elements in black powder of waste lithium iron phosphate batteries
[0036] The lithium content is 3.38%, the iron content is 26.87%, the phosphorus content is 14.73%, the aluminum content is 1.51%, the copper content is 1.32%, and the titanium content is 0.10%.
[0037] Example 1 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, the process of which is as follows: Figure 1 As shown, the following steps are included: S1. Weigh 80 g of waste lithium iron phosphate battery black powder, add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 180 g / L, homogenize for 30 min, add 82 g of concentrated sulfuric acid to adjust the pH to 1.5, and then react for 2 h to obtain the leaching solution. The quality of the waste lithium iron phosphate battery black powder leaching solution is shown in Table 2: Table 2. Statistical table of main elements in the black powder leaching solution of waste lithium iron phosphate batteries
[0038] The lithium content is 0.61%, the iron content is 4.93%, the phosphorus content is 2.59%, the aluminum content is 0.25%, the copper content is 0.19%, and the titanium content is 0.015%. The impurity removal experiment was carried out with the black powder leachate of this quality.
[0039] S2, take 200 g of leachate, add 0.42 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid alkali to adjust the pH to 3.0, and finally add 4.67 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a solution after impurity removal, the quality of which is shown in Table 3: Table 3. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0040] The lithium content is 0.53%, the iron content is 3.97%, the phosphorus content is 2.10%, the aluminum content is 0.001%, the copper content is 0.000%, and the titanium content is 0.0005%. Hydrothermal synthesis is carried out with this quality of impurity-removing liquid.
[0041] S3. Take 100 g of the impurity removal liquid, add 1.5 mmol of ascorbic acid and 300 mg of dopamine, add an appropriate amount of lithium hydroxide to adjust the lithium iron phosphorus molar ratio in the solution to 1.5:1:1, transfer the solution to a polytetrafluoroethylene reactor, and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0042] S4. Place 10 g of dry lithium iron phosphate precursor in a ceramic crucible, transfer it to the center of a tube furnace, and heat it to 500 °C at a rate of 8 °C / min under a nitrogen atmosphere. Then, keep it warm for 2 h and naturally cool it to room temperature to obtain modified lithium iron phosphate. The yield of the lithium iron phosphate composite material is calculated to be 92.09%.
[0043] Example 2 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, comprising the following steps: S1. Weigh 80 g of waste lithium iron phosphate black powder, add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 160 g / L, homogenize for 30 min, add 82 g of concentrated sulfuric acid to adjust the pH to 1.5, and then react for 2 h to obtain the leachate. The quality of the waste lithium iron phosphate battery black powder leachate is shown in Table 4: Table 4. Statistical table of main elements in the black powder leaching solution of waste lithium iron phosphate batteries
[0044] The lithium content is 0.54%, the iron content is 4.38%, the phosphorus content is 2.30%, the aluminum content is 0.22%, the copper content is 0.17%, and the titanium content is 0.013%; the impurity removal experiment was carried out with the black powder leachate of this quality.
[0045] S2, take 200 g of leachate, add 0.39 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid alkali to adjust the pH to 3.0, and finally add 4.11 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a decontaminated liquid, the quality of which is shown in Table 5: Table 5. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0046] The lithium content is 0.47%, the iron content is 3.52%, the phosphorus content is 1.90%, the aluminum content is 0.0009%, the copper content is 0.000%, and the titanium content is 0.0006%; hydrothermal synthesis is carried out using this quality of impurity-removing liquid.
[0047] S3. Take 100 g of the impurity removal liquid, add 1.5 mmol of sodium ascorbate and 200 mg of glucose, add an appropriate amount of lithium hydroxide to adjust the lithium iron phosphorus molar ratio in the solution to 1.5:1:1, transfer the solution to a polytetrafluoroethylene reactor, and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0048] S4. Place 10 g of dried lithium iron phosphate precursor in a ceramic crucible, transfer it to a tube furnace, heat it to 500 °C at a rate of 8 °C / min in a nitrogen atmosphere, then keep it warm for 2 h and naturally cool it to room temperature to obtain modified iron phosphate. The yield of lithium iron phosphate composite material is calculated to be 89.85%. Example 3 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, comprising the following steps: S1. Weigh 80 g of waste lithium iron phosphate battery black powder, add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 200 g / L, homogenize for 30 min, add 82 g of concentrated sulfuric acid to adjust pH = 1.5, and then react for 3 h to obtain a leachate. The quality of the waste lithium iron phosphate battery black powder leachate is shown in Table 6: Table 6. Statistical table of main elements in the black powder leaching solution of waste lithium iron phosphate batteries
[0049] The lithium content is 0.68%, the iron content is 5.47%, the phosphorus content is 2.88%, the aluminum content is 0.32%, the copper content is 0.25%, and the titanium content is 0.018%; the impurity removal experiment was carried out with the black powder leachate of this quality.
[0050] S2, take 200 g of leachate, add 0.57 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid alkali to adjust the pH to 3.0, and finally add 5.97 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a decontaminated liquid, the quality of which is shown in Table 7: Table 7. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0051] The lithium content is 0.59%, the iron content is 4.41%, the phosphorus content is 2.33%, the aluminum content is 0.0008%, the copper content is 0.000%, and the titanium content is 0.0003%; hydrothermal synthesis is carried out using this quality of impurity-removing liquid.
[0052] S3. Take 100 g of the impurity removal liquid, add 1.5 mmol of isoascorbic acid and 400 mg of polyvinyl pyrrolidone, add an appropriate amount of lithium hydroxide to adjust the molar ratio of lithium iron to phosphorus in the solution to 1.5:1:1, transfer the solution to a polytetrafluoroethylene reactor, and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0053] S4. Place 10 g of dry lithium iron phosphate precursor in a ceramic crucible, transfer it to the center of a tube furnace, and heat it to 500 °C at a rate of 8 °C / min under a nitrogen atmosphere. Then, keep it warm for 2 h and naturally cool it to room temperature to obtain modified lithium iron phosphate. The yield of the lithium iron phosphate composite material is calculated to be 93.73%.
[0054] Example 4 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, comprising the following steps: S1. Weigh 80 g of black powder and add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 180 g / L. After homogenization for 30 min, add 82 g of concentrated sulfuric acid to adjust the pH to 1.5. Then react for 3 h to obtain the leachate. The quality of the black powder leachate of waste lithium iron phosphate battery is shown in Table 8: Table 8. Statistical table of main elements in the black powder leaching solution of waste lithium iron phosphate battery
[0055] The lithium content is 0.61%, the iron content is 4.93%, the phosphorus content is 2.59%, the aluminum content is 0.25%, the copper content is 0.19%, and the titanium content is 0.015%; the impurity removal experiment was carried out with the black powder leachate of this quality.
[0056] S2, take 200 g of leachate, add 0.42 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid alkali to adjust the pH to 3.0, and finally add 4.67 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a decontaminated liquid, the quality of which is shown in Table 9: Table 9. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0057] The lithium content is 0.53%, the iron content is 3.97%, the phosphorus content is 2.10%, the aluminum content is 0.001%, the copper content is 0.000%, and the titanium content is 0.0005%. The impurity removal liquid of this quality is used for hydrothermal synthesis.
[0058] S3. Take 100 g of the impurity removal liquid, add 300 mg of dopamine, add an appropriate amount of lithium hydroxide to adjust the molar ratio of lithium iron to phosphorus in the solution to 1.5:1:1, transfer the solution to a polytetrafluoroethylene reactor, and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0059] S4. Place 10 g of dry lithium iron phosphate precursor in a ceramic crucible, transfer it to the center of a tube furnace, heat it to 500 °C at a rate of 8 °C / min under a nitrogen atmosphere, then keep it warm for 2 h and naturally cool it to room temperature to obtain modified lithium iron phosphate. The yield of the lithium iron phosphate composite material is calculated to be 83.86%.
[0060] Example 5 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, comprising the following steps: S1. Weigh 80 g of black powder and add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 180 g / L. After homogenization for 30 min, add 82 g of concentrated sulfuric acid to adjust the pH to 1.5. Then react for 3 h to obtain the leachate. The quality of the black powder leachate of waste lithium iron phosphate battery is shown in Table 10: Table 10. Statistical table of main element contents in black powder leaching solution of waste lithium iron phosphate battery
[0061] The lithium content is 0.61%, the iron content is 4.93%, the phosphorus content is 2.59%, the aluminum content is 0.25%, the copper content is 0.19%, and the titanium content is 0.015%; the impurity removal experiment was carried out with the black powder leachate of this quality.
[0062] S2, take 200 g of leachate, add 0.42 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid caustic soda to adjust the pH to 3.0, and finally add 4.67 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a decontaminated liquid, the quality of which is shown in Table 11: Table 11. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0063] The lithium content is 0.53%, the iron content is 3.97%, the phosphorus content is 2.10%, the aluminum content is 0.001%, the copper content is 0.000%, and the titanium content is 0.0005%; hydrothermal synthesis is carried out using this quality of impurity-removing liquid.
[0064] S3. Take 100 g of the impurity removal liquid, add 1.5 mmol of ascorbic acid, and then add an appropriate amount of lithium hydroxide to adjust the molar ratio of lithium iron to phosphorus in the solution to 1.5:1:1. Transfer the solution to a polytetrafluoroethylene reactor and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0065] S4. Place 10 g of dried lithium iron phosphate precursor in a ceramic crucible, transfer it to a tube furnace, heat it to 500 °C at a rate of 8 °C / min in a nitrogen atmosphere, then keep it warm for 2 h and naturally cool it to room temperature to obtain iron phosphate. The yield of lithium iron phosphate material is calculated to be 80.57%. Example 6 A method for regenerating lithium iron phosphate positive electrode material from waste lithium iron phosphate battery black powder, comprising the following steps: S1. Weigh 80 g of black powder and add appropriate amount of deionized water to adjust the initial solid-liquid ratio to 180 g / L. After homogenization for 30 min, add 82 g of concentrated sulfuric acid to adjust the pH to 1.5. Then react for 3 h to obtain the leachate. The quality of the black powder leachate of waste lithium iron phosphate battery is shown in Table 12: Table 12. Statistical table of main elements in the black powder leaching solution of waste lithium iron phosphate batteries
[0066] The lithium content is 0.61%, the iron content is 4.93%, the phosphorus content is 2.59%, the aluminum content is 0.25%, the copper content is 0.19%, and the titanium content is 0.015%; the impurity removal experiment was carried out with the black powder leachate of this quality.
[0067] S2, take 200 g of leachate, add 0.42 g of iron powder and stir for 30 min to remove copper, then use 4 M liquid alkali to adjust the pH to 3.0, and finally add 4.67 g of ammonium fluoride to react for 1 h to remove aluminum and titanium impurities to obtain a decontaminated liquid, the quality of which is shown in Table 13: Table 13. Statistical table of main element contents in the solution of black powder leaching solution of waste lithium iron phosphate battery after impurities removal
[0068] The lithium content is 0.53%, the iron content is 3.97%, the phosphorus content is 2.10%, the aluminum content is 0.001%, the copper content is 0.000%, and the titanium content is 0.0005%; hydrothermal synthesis is carried out using this quality of impurity-removing liquid.
[0069] S3. Take 100 g of the impurity removal liquid, add an appropriate amount of lithium hydroxide to adjust the molar ratio of lithium iron to phosphorus in the solution to 1.5:1:1, transfer the solution to a polytetrafluoroethylene reactor, and perform hydrothermal reaction at 180 °C for 4 h to obtain a lithium iron phosphate precursor.
[0070] S4. Place 10 g of dry lithium iron phosphate precursor in a ceramic crucible, transfer it to the center of a tube furnace, heat it to 500 °C at a rate of 8 °C / min under a nitrogen atmosphere, then keep it warm for 2 h and naturally cool it to room temperature to obtain lithium iron phosphate. The yield of lithium iron phosphate material is calculated to be 65.77%.
[0071] Example 7 The modified lithium iron phosphate prepared in Examples 1-6 were respectively used as positive electrode materials to assemble button batteries, and the assembly steps were as follows: the modified lithium iron phosphate was respectively mixed with a binder polyvinylidene fluoride (PVDF) and a conductive agent Super P Li in a mass ratio of 92:4:4, mixed evenly in an N-methylpyrrolidone solvent, coated on an aluminum foil, dried at 120°C, punched out, and vacuum dried at 80°C to serve as a positive working electrode, a metal lithium sheet was used as a counter electrode, and 1.0 M LiPF6 inDEC:DMC:EC (V:V:V=1:1:1) with 1% VC was used as an electrolyte system to assemble into a button battery.
[0072] Analysis and summary The electrochemical properties of the button cells prepared from the modified lithium iron phosphate in Examples 1-6 are shown in Table 14: Table 14. Comparative data of electrochemical performance of materials in various examples
[0073] The button cell assembled with the modified lithium iron phosphate prepared in Example 1 has excellent electrical performance, with a 0.1 C discharge capacity of 159.21 mAh / g, a 1 C discharge capacity of up to 145.33 mAh / g, and a capacity retention rate of 91.28%. This is because during the synthesis of the modified lithium iron phosphate, ascorbic acid is used to avoid the oxidation of ferrous ions, and the use of dopamine carbon source with good film-forming properties avoids the problem of uneven coating, thereby effectively improving the performance of the modified lithium iron phosphate positive electrode material.
[0074] The button cell assembled with modified lithium iron phosphate prepared in Example 2 has good electrical performance, with a 0.1 C discharge capacity of 161.18 mAh / g, a 1 C discharge capacity of 139.52 mAh / g, and a capacity retention rate of 86.56%. This is because sodium ascorbate is used in the synthesis process of the modified lithium iron phosphate to avoid the oxidation of ferrous ions, but less glucose carbon source is used. Although the coating is uniform, the overall carbon content is low, resulting in a low 1C discharge capacity.
[0075] The button cell assembled with modified lithium iron phosphate prepared in Example 3 has good electrical performance, with a 0.1 C discharge capacity of 156.66 mAh / g, a 1 C discharge capacity of 147.39 mAh / g, and a capacity retention rate of 94.08%. This is because the use of isoascorbic acid in the synthesis process of the prepared modified lithium iron phosphate avoids the oxidation of ferrous ions, but the use of too much polyvinyl pyrrolidone carbon source has a high overall carbon content, which reduces the proportion of effective materials and results in a low 0.1C discharge capacity.
[0076] The modified lithium iron phosphate assembled button battery prepared in Example 4 has average electrical performance, with a 0.1 C discharge capacity of 154.36 mAh / g, a 1 C discharge capacity of only 128.19 mAh / g, and a capacity retention rate of 83.04%. This is because no antioxidant was used during the synthesis process to prevent the oxidation of ferrous ions, resulting in a low sample purity.
[0077] The lithium iron phosphate assembled button battery prepared in Example 5 has average electrical performance, with a 0.1 C discharge capacity of 162.23 mAh / g, a 1 C discharge capacity of 117.89 mAh / g, and a capacity retention rate of 72.67%. This is because the carbon source was not used for coating during the synthesis process, resulting in poor conductivity.
[0078] The button cell assembled with lithium iron phosphate prepared in Example 6 has poor electrical performance, with a 0.1 C discharge capacity of 151.83 mAh / g, a 1 C discharge capacity of 101.45 mAh / g, and a capacity retention rate of 66.81%. This is because antioxidants and carbon coating materials were not used in the synthesis process of the prepared lithium iron phosphate, resulting in poor electrical performance.
[0079] As can be seen from the above data, the present invention adjusts and optimizes the leaching and impurity removal process parameters of waste lithium iron phosphate battery black powder, realizes almost complete removal of impurities such as aluminum, copper, and titanium, significantly improves the purity of the leachate, reduces its potential negative impact on battery performance, and provides a good foundation for subsequent processes. In addition, the dosage of antioxidants is reasonably controlled to prevent the oxidation of ferrous ions, ensure the chemical stability of the material and battery performance, adjust the dosage of carbon coating agents, ensure uniform coating, and avoid affecting the proportion of effective materials and battery performance due to excessive carbon content; by finely controlling the dosage of antioxidants and carbon coating agents, and optimizing carbonization process parameters, the best carbon coating effect is achieved, further promoting the performance improvement of regenerated lithium iron phosphate materials, thereby significantly improving the electrochemical performance of the battery. The present invention effectively improves the reuse value of waste lithium iron phosphate battery black powder through systematic process optimization and material selection, and provides a feasible path for preparing high-performance regenerated lithium iron phosphate batteries. This not only helps to recycle resources, but also has important significance for environmental protection and sustainable development.
[0080] It should be understood that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.
Claims
1. A method for regenerating lithium iron phosphate positive electrode materials from waste battery black powder, characterized in that: The following steps are involved: S1, leaching: put the waste lithium iron phosphate battery black powder in a beaker, add deionized water for homogenization, add sulfuric acid to adjust the pH value and react, and filter to obtain a leachate rich in lithium, iron, phosphorus and impurity elements; S2, impurity removal: according to the impurity copper content in the leachate obtained in step S1, 1-3 times the molar amount of reduced iron powder is added to remove copper impurities by replacement reaction, the pH value is adjusted to 2-6 with a pH regulator, and according to the impurity aluminum content in the leachate, 1-6 times the molar amount of a complexing agent is added to remove impurities such as aluminum and titanium; S3, synthesis: placing the solution after impurity removal in step S2 in a reactor, adjusting the molar ratio of Li:Fe:P in the solution to 1-3:1:1, adding 0-3 mmol antioxidant and 0-800 mg carbon coating agent, stirring evenly and sealing the solution and placing it in an oven for hydrothermal reaction, and filtering and drying the solution after the reaction is completed and the temperature is naturally lowered to obtain a lithium iron phosphate precursor; S4, carbonization: placing the lithium iron phosphate precursor obtained in step S3 in a crucible, transferring it to a sintering device, heating it to 400-600°C at a rate of 5-10°C / min under the protection of an inert atmosphere, keeping it at that temperature for 1-4 hours, and then naturally cooling it to room temperature to obtain modified lithium iron phosphate.
2. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 1, characterized in that: In step S1, the solid-liquid ratio of waste lithium iron phosphate battery black powder to deionized water is 100-200 g / L; the homogenization treatment time is 30-45 min; the pH value is 1-3; and the reaction time is 1-3 h.
3. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 2, characterized in that: In step S1, the solid-liquid ratio of waste lithium iron phosphate battery black powder to deionized water is 160-200 g / L; the pH value is 1-2; and the reaction time is 1-2 h.
4. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 1, characterized in that: In step S2, the molar ratio of the added amount of reduced iron powder to the impurity copper is 1-2; the pH regulator includes ammonia water, sodium hydroxide or sodium carbonate solution; and the complexing agent includes hydrofluoric acid, sodium fluoride or ammonium fluoride.
5. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 1, characterized in that: In step S3, the molar ratio of Li:Fe:P in the adjustment solution is 1-2:1:1; the antioxidant includes ascorbic acid, sodium ascorbate or isoascorbic acid; the amount of the antioxidant added is 1-2 mmol; the carbon coating agent includes polyvinyl pyrrolidone, dopamine or glucose; the amount of the carbon coating agent added is 100-400 mg; the temperature of the hydrothermal reaction is 160-200 ° C, and the reaction time is 2-6 h.
6. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 5, characterized in that: In step S3, the temperature of the hydrothermal reaction is 160-180°C, and the reaction time is 2-5 h.
7. The method for regenerating lithium iron phosphate positive electrode material from waste battery black powder according to claim 1, characterized in that: In step S4, the inert atmosphere includes nitrogen, argon or argon-hydrogen mixed gas; the heating rate is 5-9°C / min, the insulation temperature is 450-600°C, and the insulation time is 1-3 h.
8. Use of the modified lithium iron phosphate as claimed in any one of claims 1 to 7 as a positive electrode material in a lithium ion battery.
9. The use of the modified lithium iron phosphate as a positive electrode material in a lithium ion battery according to claim 8, characterized in that: The invention comprises the following assembly steps: mixing the modified lithium iron phosphate with a binder and a conductive agent in a mass ratio of 92:4:4, slurrying them evenly in an N-methylpyrrolidone solvent, coating them on an aluminum foil, drying them at 120°C to punch out sheets, vacuum drying them at 80°C to use them as positive working electrodes, using a metal lithium sheet as a counter electrode, and using 1.0 M LiPF6 in DEC:DMC:EC (V:V:V=1:1:1) with 1% VC as an electrolyte system to assemble button cells.
10. The use of the modified lithium iron phosphate according to claim 9 as a positive electrode material in a lithium ion battery, characterized in that: The adhesive includes polyvinylidene fluoride; the conductive agent includes Super P Li.
Citation Information
Patent Citations
Method for recovering lithium from lithium iron phosphate
CN114318009A
Method for recycling regenerated lithium carbonate from lithium iron phosphate waste
CN114906862A
Regeneration method of positive electrode material of waste lithium iron phosphate battery
CN116119636A
Cited By
Recycling method of invalid lithium iron phosphate black powder
CN120483080A
Regenerated lithium iron phosphate and preparation method thereof
CN122393290A